The hazardous interactions of copper-dyed patient gowns with MRI: Two cases of superficial abdominal burns - Gyeong Rip Kim; Hyun Hwa Im; Jang Seon Yoo; Da Jeong Baek; Gyeong Hwan Kim; Seong Jin Jin; In Jun Je; Jong Hyeok Kwak (Radiology Case Reports, 2023)
Magnetic resonance imaging is a commonly used imaging modality in medical procedures. Despite its prevalent use, unexpected adverse events such as burns can occur during an MRI procedure. The majority of the transmitted Radio Frequency power can be converted into heat within the patient's tissue due to resistive losses, leading to such incidents. In this study, we present an intriguing case of a patient who experienced an MRI-induced burn, presumably caused by the copper dye in the patient's gown. Notably, we observed frequent distortion of the MR image due to the patient's gown. The awareness and understanding of such potential adverse events are critical for clinicians and technicians to prevent future occurrences. Through this study, we aim to contribute to this critical area of patient safety during MRI procedures.